Foraging ecology of birds in mudflat area of Tanjung Laboh, Johor - Fauzi, N. A. (2021)
Tanjung Laboh is located in one out of three Important Bird Areas (IBAs) in Johor called South West Johor Coast which is very crucial foraging ground for resident and migratory shorebirds. However, the airfield development plan located in the area have been an issue as it might disturbed the foraging ecology of the shorebirds. Therefore, it is necessary to analyse the food resources present and the foraging behaviour of the shorebirds in order to determine the effect of disturbance towards the shorebirds’ foraging behaviour. Thus, a study was conducted for a month (July to August 2018) in the mudflat area of Tanjung Laboh to identified the time spent of foraging, food selection and foraging technique of shorebirds by using direct observation method. A total of 212 observations were recorded during sampling period. No significant differences were found in time spent foraging between the bird species, (F = 0.18, p = 0.946). ASpearmanRankCorrelation proved that there is no significant relationship between the time spent of foraging and the number of preys taken by each species (R= 0.436, p > 0.05). Based on observation, fish is the most preferred diet choice among bird species which counts a total of 57% followed by unknown (20%), worm (19%) and bivalve (4%). Significant correlation was found between the abundance of bird and the frequency of disturbances (humans, dogs and vehicles) (p < 0.05) while human contribute to a higher percentage in disruptions towards the species studied (57.7%). The responses of the birds towards the disturbances were varied in this study, however the birds tend to choose foraging ground far from disturbance area as the disturbances might chase birds’ prey away thus reduce their feeding rate. By understanding how the shorebirds response toward disturbance, the conservation action can be enforced in the future.